PENDAMPINGAN PENYUSUNAN PERENCANAAN SISTEM PENGANGKUTAN SAMPAH TERPADU DI DESA PAMPANGAN KABUPATEN OGAN KOMERING ILIR - Eka Susanti; Indrawati; Oki Dwipurwani; Endro Setyo Cahyono; Robinson Sitepu (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2023)
The service activity for planning an integrated waste transportation system was carried out in Pampangan Village, Pampangan District, Ogan Komering Ilir, South Sumatra. The unavailability of integrated waste transportation facilities in Pampangan is the rationale for community service activities. The purpose of the activity is to provide assistance in preparing a plan for an integrated waste transportation system in Pampangan. The planning made is related to the facilities for transporting waste and the location of the TPA (final disposal site). Based on the results of the waste sample, the estimated amount of waste generated every day is 1000 kg. Using goal programming and linear programming, a wooden cart with a maximum capacity of 15 kg and 25 kg can transport waste 6 times and 26 times, respectively. Based on the calculation of total transportation, a waste transportation vehicle with a capacity greater than the currently available means of transportation is required.